The potential of electronic medical record systems to support quality improvement work and research in Norwegian general practice - Treweek Shaun (BMC, 2003)
Abstract Background Electronic medical record (EMR) systems are used for many purposes including patient care, administration, research, quality improvement and reimbursement. This study aimed to test a data extraction tool (QTools) and to provide information to support the interpretation of EMR data. Methods Comparison of aggregated practice data for selected EMR fields and interviews with practice staff. Practices received summaries of their data and aggregated data for other practices. Summaries were discussed in interviews. Results Fourteen general practices in the Oslo area using the Winmed EMR participated. QTools ran successfully at all 14 practices. Nine practices agreed to interviews. Apart from age and sex, general patient information was poorly recorded. Face-to-face consultations account for 59% of contacts but differences in coding led to variations between practices. Psychiatric problems accounted for 13% of diagnoses, other diagnosis groups rarely accounted for more than 5%. Over 90% of diabetics and 75% of patients with heart disease were identified by diagnosis code alone. Conclusion Some variation seen in EMR data is due to differences in the way staff use their EMR. These data can support quality improvement work but this requires an awareness of how the EMR is actually used by practice staff.